Purinergic signalling in bone - Rumney, Robin M.; Wang, Ning; Agrawal, Ankita; Gartland, Alison (Frontiers in Endocrinology, 2012)
Purinergic signalling in bone was first proposed in the early 1990s with the observation that extracellular ATP could modulate events crucial to the normal functioning of bone cells. Since then the expression of nearly all the P2Y and P2X receptors by osteoblasts and osteoclasts has been reported, mediating multiple processes including cell proliferation, differentiation, function and death. This review will highlight the most recent developments in the field of purinergic signalling in bone, with a special emphasis on recent work resulting from the European Framework 7 funded collaboration ATPBone, as well as Arthritis Research UK and Bone Research Society supported projects.